ROLE OF ULTRASOUND AND MAGNETIC RESONANCE IMAGING IN DIAGNOSIS OF OVARIAN AND DEEP ENDOMETRIOSIS - T. A. Gromova; S. A. Levakov; T. D. Guriev (IRBIS LLC, 2017)
Endometriosis is common among women of reproductive age. Due to its nonspecific clinical picture, a correct diagnosis of endometriosis is especially important in developing an effective treatment plan. Ultrasound and magnetic resonance imaging with correct interpretation, and combined with differential diagnosis, is essential for determining the location and spread of endometriosis, which helps optimize the surgical treatment.